Letter (copy) : Spanish Medical Aid Committee - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0074-001 4th March, 1938. Dear Churchill, SPANISH MEDICAL AID COMMITTEE. I am writing to you unofficially at the request of the Committee, to enquire as to the present and the future with regard to yourself and the position of the Committee. We have heard nothing of you for over two months — and I think you will agree that the present position cannot go on and needs clarification and perhaps reorganisation. Before coming to any decision, however, we would like to hear from you, and have your views. In your absence we have been without an official representative in Spain and without one of our Treasurers. We have been patiently waiting to hear from you. I will be glad if you can see your way to reply to this letter as soon as possible, as in a short time - say another ten days - it is imperative that we should come to some definite decision as to our future arrangements for representation, etc., in Spain, in order to facilitate our plans and our policy. Yours sincerely, 292C/946/2/74